Metabolic Stress-Induced Activation of AMPK and Inhibition of Constitutive Phosphoproteins Controlling Smooth Muscle Contraction: Evidence for Smooth Muscle Fatigue? - Smith, Corey A.; Miner, Amy S.; Barbee, Robert W.; Ratz, Paul H. (Frontiers in Physiology, 2017)
Metabolic stress diminishes smooth muscle contractile strength by a poorly defined mechanism. To test the hypothesis that metabolic stress activates a compensatory cell signaling program to reversibly downregulate contraction, arterial rings and bladder muscle strips in vitro were deprived of O2 and glucose for 30 and 60 min (“starvation”) to induce metabolic stress, and the phosphorylation status of proteins involved in regulation of contraction and metabolic stress were assessed in tissues under basal and stimulated conditions. A 15-30 min recovery period (O2 and glucose repletion) tested whether changes induced by starvation were reversible. Starvation decreased basal phosphorylation of myosin regulatory light chain (MLC-pS19) and of the rho kinase (ROCK) downstream substrates cofilin (cofilin-pS3) and myosin phosphatase targeting subunit MYPT1 (MYPT1-pT696 and MYPT1-pT853), and abolished the ability of contractile stimuli to cause a strong, sustained contraction. Starvation increased basal phosphorylation of AMPK (AMPK-pT172) and 3 downstream AMPK substrates, acetyl-CoA carboxylase (ACC-pS79), rhoA (rhoA-pS188) and phospholamban (PLB-pS16). Increases in rhoA-pS188 and PLB-pS16 would be expected to inhibit contraction. Recovery restored basal AMPK-pT172 and MLC-pS19 to control levels, and restored contraction. In AMPKalpha2 deficient mice (AMPKalpha2-/-), the basal level of AMPK-pT172 was reduced by 50%, and MLC-pS19 was elevated by 50%, but AMPKalpha2-/- did not prevent starvation-induced contraction inhibition nor enhance recovery from starvation. These results indicate that constitutive AMPK activity participates in constitutive regulation of contractile proteins, and suggest that AMPK activation is necessary, but may not be sufficient, to cause smooth muscle contraction inhibition during metabolic stress.